Perceived Brand Localness vs Social Media: Analysis of Effectiveness in Shaping Consumer Preferences for Heritage Coffee Shops - Sudirman, Sudirman; Dina Octaviani; Windi Pratiwi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the influence of perceived brand localness and social media promotion on consumer purchase intention with brand attitude as a mediating variable in legendary local coffee shops. The digital era has transformed the marketing landscape, yet heritage coffee shops with strong cultural roots demonstrate extraordinary resilience amid competition with modern coffee shops. This phenomenon raises questions about how perceived brand localness and social media promotion influence consumer purchase intention in heritage brand contexts. The study employs a quantitative approach with survey method on 150 respondents from one of the legendary coffee shop consumers in Pontianak City selected through purposive sampling. Data were analyzed using Structural Equation Modeling with Partial Least Square approach. Results show that perceived brand localness has a positive significant effect on brand attitude and purchase intention. Social media promotion positively influences brand attitude but has no direct effect on purchase intention. Brand attitude mediates the relationship between perceived brand localness and purchase intention, but does not mediate the relationship between social media promotion and purchase intention. Findings confirm that for heritage coffee shops, perceived brand localness is more effective than social media promotion in driving purchase intention. This research provides strategic insights for heritage brands in optimizing local strength while leveraging digital marketing as brand builder.